Advances in synthesis, properties and emerging applications of tin sulfides and its heterostructures. (12th October 2020) - Shinde, Pratik; Rout, Chandra Sekhar
Abstract : The tin sulfide (Sn x S y ) class of materials has attracted tremendous research interest owing to their intriguing physicochemical properties. In this review, we explore the recent progress in their synthesis, properties, and applications. Abstract : The tin sulfide (Sn x S y ) class of materials has attracted tremendous research interest in recent years owing to their intriguing physicochemical properties. Their inimitable optical, electronic, and mechanical properties open up windows for a broad range of promising applications. The precise design and tuning of the crystal phase, size, thickness, and composition holds excellent potential for utilizing them as crucial components of advanced devices. In this review, we explore the recent progress in their synthesis, properties, and applications. Initially, we outline the Sn x S y class of materials briefly and discuss the recent developments in their phase and crystal dependent physicochemical properties. Numerous strategies have been portrayed for the preparation of single- to multi-layer, zero dimension to three dimension, and nano-sized to micro-sized materials. In-depth information on synthesis methods has been explored under the top-down and bottom-up approaches. The review includes the properties and synthesis of tin sulfides and also delivers exciting progress in various fields of applications. Finally, the prospects and opportunities in these exciting fields are discussed, based on their current progress.